Proceedings of ELM-2015 Volume 1 Theory, Algorithms and Applications (I) - Cao, Jiuwen; Mao, Kezhi; Wu, Jonathan; Lendasse, Amaury (Proceedings in Adaptation, Learning and Optimization, 2016)
This book contains some selected papers from the International Conference on Extreme Learning Machine 2015, which was held in Hangzhou, China, December 15-17, 2015. This conference brought together researchers and engineers to share and exchange R&D experience on both theoretical studies and practical applications of the Extreme Learning Machine (ELM) technique and brain learning. This book covers theories, algorithms ad applications of ELM. It gives readers a glance of the most recent advances of ELM. .